Case Report: A Rare Case of an Obstructed Floating Kidney Incarcerated Within a Massive Scrotal Hernia: Management at a Norwegian Hospital by Surgeons With Experience in Africa - Robbert-Jan Lindeman; Chris Oppong; Odd Mjåland (Journal of Abdominal Wall Surgery)
Open mesh repair for inguinal hernia is one of the most commonly performed surgical procedures worldwide. Pediatric and symptomatic inguinal hernias are preferably treated at an early stage, according to current guidelines. Consequently, massive inguinoscrotal hernias are rarely seen in most high-income countries. In contrast, scrotal hernia repair account for 67% of all inguinal hernia repairs in low-resource countries. Recently, there has been an increased focus on scrotal hernias as a specific type of pathology. Alterations of anatomical landmarks and disruption of anatomical layers make these hernias a surgical challenge, requiring a different surgical approach. Due to the rarity in high resource countries, most general surgeons have limited experience in their surgical management. In this case report we present a challenging acute case of massive inguinoscrotal hernia with incarceration of the right kidney. The authors of this paper are part of the Norwegian-British team for Operation Hernia, a UK-based humanitarian Trust with 18 years of experience in hernia surgery in low resource countries. Through the years, the team has gathered extensive experience in the management of large inguinoscrotal hernias. This paper describes the management of a complex case, which was treated with the combined experience of frugal surgery on Operation Hernia missions and the almost limitless resources in a Norwegian hospital.